Monstress. Volume eight, Inferno - Liu, Marjorie M. (Image Comics, Inc., 2023)
"The truth about the death of Maika's mother has been revealed, and Maika has come undone. As her allies scramble to save her soul, they find themselves in the unlikeliest of places--the beautiful and brutal prison planet where the Monstra have long been locked away. This visit to the site of Zinn's worst nightmares might just hold the key to Maika's survival--and to the long-buried origins of the Known World"--Back cover.